AWARENESS OF RADIATION INDUCED ORAL DAMAGE AMONG DENTAL STUDENTS - Vijaya Kumaran, Ghayathri; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to assess the knowledge and attitudes regarding radiation-induced oral damage amongst the dental students. The purpose of this study is to create awareness and determine the understanding of radiation-induced oral damage among dental students. This study was conducted based on a questionnaire that consisted of 10 questions through a web-linked application called Survey Monkey. A convenient sample size of 100 consecutive dental students who are currently practicing in Chennai participated in the study. As an overall result, most of the participants are aware of radiation-induced oral damage. As a conclusion, the awareness of radiation-induced oral damage and development among dental students in Chennai is adequate, but certain knowledge has to be brushed up among them for a higher level. Furthermore, they need to be trained on these grounds to help them treat their patients with more consent and awareness.